A dignidade da pessoa humana como eixo interpretativo da persecução criminal: meios consensuais de solução de conflitos como instrumentos de ressignificação do papel da vítima - Pompeo, Monize Flavia (2022)
This paper seeks to analyze the consensual model of criminal justice as a viable option, given the current crisis in the penal system, highlighting the construction of a new conflict resolution system reflecting the ideals brought by victimological movements, based on the dignity of the human person, providing due respect to victims of crime, looking out for their interests, avoiding secondary victimization. To achieve the proposed objectives, the method used was logical-deductive and the technique adopted was bibliographical and jurisprudential research, with a theoretical and descriptive approach, starting from the premise that the current retributive-punitive model does not integrate the victim to the resolution of criminal conflicts and the consensual model enables the victim's participation in the criminal procedure, being compatible with the Brazilian reality. It starts from the principle of inclusion and valuing of the victim, but without neglecting the rights and guarantees of the accused, analyzing the protagonism of those who had their legal interests offended in the development of effective criminal policies for the resolution of the criminal conflict, supported by the dialogue between the parties. It is intended to analyze the principles, values and foundations of the consensual model of criminal justice, to understand the feasibility of the consensual proposal, with the rescue of the effective participation of the offended party in the process, to be guaranteed by the member of the Public Ministry. Observations are prepared from the ministerial perspective in consensual activity, with a more resolute profile, facing the myth of the mandatory principle, demonstrating that the performance of Parquet, although endowed with a margin of discretion arising from the consensual criminal logic, is not unrestricted, finding limits on criminalization warrants, which elect relevant legal assets that are non-negotiable. Finally, the Brazilian reality is presented with a critical analysis of the business criminal justice model introduced in art. 28- A of the Code of Criminal Procedure by Law No. 13.964/2019. A study will be carried out on the normative rules, requirements and conditions for the application of the Penal NonPersecution Agreement, presenting the details of the new alternative form of criminal prosecution and problematic issues involving the expansion of commercial criminal justice in the Brazilian legal system. In relation to what was investigated, the limits of the renunciation of fundamental rights and guarantees are examined, arguing for the absence, in abstract, of coercion in non-prosecution agreements, in compliance with self-determination and the dignity of the human person. It denies an affront to the right to silence and nemo tenetur in nonprosecution agreements. In addition, it will be studied how the non-criminal prosecution agreement can be a means of promoting victims' rights if dialogues are carried out with restorative practices, concluding by the feasibility and relevance of this dialogue considering the policies to encourage self-composition and valorization of the victim, giving a more humanizing effect to the criminal process, transforming the way in which the crime, the criminal and the importance of the participation of the parties in the resolution of the criminal conflict, especially the victim